Quality Index and Land Suitability for Cocoa Plants in Bandar District, Pacitan Regency, East Java - Supriyadi Supriyadi; Rahayu Rahayu; Dwi Priyo Ariyanto; Dianika Prastiwi (Institut Pertanian Bogor, 2026)
Cocoa (Theobroma cacao L.) is an Indonesian plantation crop that has potential for agricultural development. The goal of this study was to evaluate the relationship between soil quality index (SQI) and land suitability in Bandar District, Pacitan Regency, East Java for cocoa plants, as well as to identify the limiting variables and inputs used to boost cocoa plant production. This study used a descriptive survey and purposive soil sampling methods. Land Map Units (LMUs) were created by overlaying maps of soil type, land use, slope, and rainfall. To generate Principal Component (PC) data, SQI calculations utilized the expert judgement and Principal Component Analysis (PCA) methodologies. PC was utilized to select the Minimum Data Set (MDS); the PC chosen as the MDS had an eigenvalue near to 1 or −1 or a p-value less than 0.05 or 5%, and the SQI value was determined. Land suitability was assessed using the FAO land evaluation framework (1976). The study site SQI ranged from very low (1.76) to low (3.14), with a land suitability class of S3 (marginally suitable). association study revealed a substantial positive association between SQI and land suitability (r = 0.688, p = 0.000). The correlation test's limiting indicator, P, was available. Liming, adding organic materials, and fertilization are all recommended improvements. Keywords: cocoa, land suitability evaluation, soil quality index